Kautilya's concept of diplomacy : a new interpretation - Mukherjee, Bharati, 1942- (Minerva Associates (Publications), 1976)
Study of the concept as expounded in Arthaśāstra, ancient work on Indian polity, by Cāṇakya, also known as Kauṭalya.